ASSOCIATION OF RS2200733 POLYMORPHISM WITH ANTIARRHYTHMIC THERAPY AND PROGRESSION OF ATRIAL FIBRILLATION IN THE UZBEK POPULATIO - R. D. Kurbanov; G. Zh. Abdullaeva; T. Z. Ganiev; A. A. Abdullaev; N. U. Zakirov (Евразийский Кардиологический Журнал)
Aim: to study the association of rs2200733 polymorphism with antiarrhythmic efficacy of amiodarone, propafenone and allapinin in the prevention of atrial fibrillation (AF) progression.Material and methods. In order to comparatively evaluate the effectiveness of antiarrhythmic drugs in the prevention of AF progression the analysis included 163 patients (54 (33.1%) – with persistent AF and 109 (66,9%) with paroxysmal) in age from 31 to 77 years (average age 52.16±12.64 years) with an initially restored sinus rhythm (pharmacological or electric cardioversion). To prevent relapse of AF one of the antiarrhythmic drugs (amiodarone, propafenone or allapinin) was recommended to patients. In order to identify the association of rs2200733 polymorphism in ATFB5 gene with AF the study included 69 patients who were initially diagnosed with paroxysmal (n=20) and persistent AF (n=49). The control group (n=30) consisted of individuals of Uzbek nationality without AF in age from 30 years to 77 years. Genotyping of samples for the allelic carriage of rs2200733 polymorphism was performed by PCR-RFLP. The results are presented as M ± SD.Results. It was shown that a persistent form of AF is prognostically unfavorable for AF progression. Moreover, in patients with AF progression the initial body mass index was significantly higher and a higher risk of  developing heart failure was observed in the dynamics. The results indicate the predominance of the CC genotype and C allele of rs2200733 polymorphism in Uzbek patients with AF. A similar analysis performed in the control group (without AF) also showed a significant prevalence of the C allele and CC genotype. The association of TT genotype with a risk of AF was shown, since AF was more common among TT genotype carriers compared with CT and CC genotypes carriers (90% versus 67%, p<0.001). The limiting effect of TT carriage on the antiarrhythmic efficacy of the reference drug, amiodarone, in patients with AF was also noted.Conclusion. Thus, our study showed that the TT genotype of rs2200733 polymorphism is a genetic marker of the AF risk in Uzbek population. Carriers of TT genotype of rs2200733 polymorphism also have the most unfavorable prognosis for AF progression. Genotyping of the rs2200733 polymorphism in Uzbek patients with AF will allow differentially prescribing antiarrhythmic drugs and timely conduct procedure for radical elimination of arrhythmogenic substrate using radiofrequency ablation.